2009
DOI: 10.1021/jm9016224
|View full text |Cite
|
Sign up to set email alerts
|

Corrections to Design, Synthesis, and Biological Evaluation of 6α- and 6β-N-Heterocyclic Substituted Naltrexamine Derivatives as μ Opioid Receptor Selective Antagonists

Abstract: Page 1418. Lines 3-6 in the right column should be as follows:Molecular Design. On the basis of the molecular modeling study, two series of ligands were designed as MOR selective antagonists (Table 1). While some of these ligands have been reported previously for various purposes (e.g. control compound 8, 1 compounds 2 and 8, 2,3 and control compounds 15 and 16, 4 ), to our knowledge none of them have been discussed specifically in the literature as selective μ opioid receptor antagonists.References for the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 2 publications
0
47
0
Order By: Relevance
“…To determine whether these compounds may be centrally acting, a tail immersion assay was conducted to find out whether dMNAP and dMNMP produced antinociception or blocked morphine's antinociceptive effects by subcutaneous injection (s.c.). 39,42 As observed in Figure 2A, dMNAP at a dose of 10 mg/kg produced insignificant antinociception compared to morphine (10 mg/kg). dMNMP, on the other hand, did not produce antinociception and its %MPE (the percentage maximum possible effect) was not significantly The values are the mean ± SEM of at least three independent experiments.…”
Section: ■ Introductionmentioning
confidence: 64%
“…To determine whether these compounds may be centrally acting, a tail immersion assay was conducted to find out whether dMNAP and dMNMP produced antinociception or blocked morphine's antinociceptive effects by subcutaneous injection (s.c.). 39,42 As observed in Figure 2A, dMNAP at a dose of 10 mg/kg produced insignificant antinociception compared to morphine (10 mg/kg). dMNMP, on the other hand, did not produce antinociception and its %MPE (the percentage maximum possible effect) was not significantly The values are the mean ± SEM of at least three independent experiments.…”
Section: ■ Introductionmentioning
confidence: 64%
“…Previous studies using morphine in the same protocol showed a sixfold development of tolerance to i.c.v. morphine (30).…”
Section: Resultsmentioning
confidence: 99%
“…1) that selectively activates heteromeric μ/κ-opioid receptors in HEK-293 cells. Moreover, NNTA exhibits potent antinociception and lack of physical dependence or conditioned place preference in mice (28)(29)(30).…”
mentioning
confidence: 99%
“…13−16 Briefly, NAP behaved as a low efficacy MOR partial agonist in the [ 35 S]GTPγS binding assay whereas it also competitively inhibited MOR full agonist [D-Ala 2 -MePhe 4 -Gly(ol) 5 ]enkephalin (DAMGO)-stimulated [ 35 S]GTPγS binding. 13,15 Interestingly, NAP produced no apparent analgesic effects at doses up to 100 mg/kg, while it could antagonize the antinociceptive effect of morphine in the warm water tailimmersion assay with moderate potency. 13 Furthermore, being a P-glycoprotein substrate, NAP has limited access to the central nervous system and dose-dependently restored morphine-impaired intestinal motility without precipitating significant withdrawal symptoms (jumps, wet-dog shakes, or locomotion).…”
mentioning
confidence: 98%
“…13,15 Interestingly, NAP produced no apparent analgesic effects at doses up to 100 mg/kg, while it could antagonize the antinociceptive effect of morphine in the warm water tailimmersion assay with moderate potency. 13 Furthermore, being a P-glycoprotein substrate, NAP has limited access to the central nervous system and dose-dependently restored morphine-impaired intestinal motility without precipitating significant withdrawal symptoms (jumps, wet-dog shakes, or locomotion). 14,16 While originally NAP was defined as a potent antagonist on the MOR due to its lack of efficacy from our in vivo studies, its partial agonism on the MOR from the in vitro experiment results really intrigued us.…”
mentioning
confidence: 98%